Scenarios and strategy - Schoemaker, Paul J. H. (Henry Stewart Talks, 2013)
Levels of strategic planning, Scenario planning and multiple ways to leverage it, Building blocks for scenarios, Scenario development process -GM’s mental model (circa 1968), Applying the concepts in practice, The future of credit unions, Basic scenario matrix, Two dimensions of uncertainty, How to profit from uncertainty, Talent and leadership strategies, Stress testing strategy, Options portfolio, Key concepts of platform for innovation, Monitoring key uncertainties and linking the scanning to scenarios, Breaking down the strategic messages, Stakeholder management, Expanding your tool kit
Reviewed at 2018/04/30